"Systematic inquiry for energy security and sustainability"(a case study approach for India using SAP-LAP framework). Issue 3 (7th November 2016) - Soni, Vivek; Singh, S.P.; Banwet, Devinder Kumar
Abstract : Purpose: Energy supply delivered via various energy projects is an important aspect of energy security for India. Managing supply through various capacity additions for providing continuous electricity 24×7 by 2019 is a significant challenge for the country. In this context, there is a need to assess the present situation of energy generation from the traditional energy projects that are being installed for the purpose of capacity addition. Thus, the purpose of this paper is to develop an inquiry model based on situation-actor-process (SAP), learning-action-performance (LAP) for the Indian energy and power sectors to analyze the status of the supply side of energy security. Design/methodology/approach: A SAP-LAP model is used to synthesize the situations of both the energy and power sectors. For both systems, inquiry- and matrices-based SAP-LAP models have been considered for this purpose. The situation is presented for various issues related to the execution of different types of energy projects. Actors in these sectors are classified by those who are responsible and engaged in the execution of various energy projects. For demonstration purposes, only a thermal energy project is highlighted in this case study. Based on the synthesis of SAP elements, various LAP elements are analyzed which leads to lessons that may be learnt from the case. Suitable actions are identified, followed by an assessment of their impact on the performance of the energy projects. Findings: By developing a framework for a SAP-LAP model for the assessment of energy security, it was found that both sectors need more investment for their sustainable growth and that the actors identified should be proactive in their decision making. Decision making should be based on the sustainable management practices of life cycle management and life cycle costing for the better utilization of energy resources to strengthen overall energy security. Research limitations/implications: The SAP-LAP analysis is used to explain the supply side of energy security in a managerial context, as applied in the case of the Indian energy and power sectors. However, some other quantitative multiple-criteria decision-making techniques like the preference ranking organization method for enrichment of evaluations, the complex proportional assessment of alternatives, the analytic hierarchy process or qualitative interactions assessment techniques such as interpretive structural modeling (ISM), total interpretive structural modeling (TISM) or the interpretive ranking process can also be explored for the development of an energy security framework. Practical implications: The synthesis of SAP leads to LAP, which bridges the gap by suggesting improvement actions based on learning from the present situation of power supply, from actors in the industry and from existing processes. The model presents the situation of energy security in terms of the timely execution of energy projects and their impacts on the gross domestic product of the country. Social implications: The framework for learning can provide information to the various stakeholders, investors and sector organizations inquiring about various issues related to energy projects and supporting the idea for energy security and sustainability. Originality/value: The SAP-LAP model is a novel approach for analyzing the present status of energy supply performance in a single model, which can act as the support for decision making in conflicting situations, specifically the conflicting nature of the Indian energy and power sectors.